The performance of export credit agencies in post-communist Central European countries - Karel Janda; Eva Michalíková; Lucia Psenakova (Charles University in Prague, Institute of Economic Studies (IES), 2013)
This paper is the first one to analyze official government export promotion in all four post-communist Central European Visegrad countries (Czech Republic, Hungary, Poland, Slovakia). Similar development of those economies in transition period after the fall of communism is described and their extremely fast and successful reorientation towards Western markets is emphasized. Nowadays each government in the region implements its own export strategy, where interestingly each country defines different priority territories for their export. The core of this paper is analysis of export credit agencies in Visegrad countries. Firstly we compare advantages and disadvantages of different forms of export credit agencies. Then we apply empirical data from international trade in gravity model framework and we conclude that the most effective type of export credit agency in Visegrad Four region is currently Polish KUKE which is an institution operating in the form of an insurance company. Other forms such as a bank and an institution providing both insurance and financing facilities are currently less effective. We confirm that smaller distance and higher GDP increase the amount of export in line with basic intuition of a gravity model of international trade.
Keywords: F14; G28; C23; 330; international trade; state promotion; export credit agencies; gravity model; Visegrad Group